2012
DOI: 10.1038/srep00801
|View full text |Cite
|
Sign up to set email alerts
|

Size effects in Atomic-Level Epitaxial Redistribution Process of RuO2 over TiO2

Abstract: Controls over the atomic dispersity and particle shape of noble metal catalysts are the major qualities determining their usability in industrial runs, but they are usually difficult to be simultaneously realized. Inspired from the Deacon catalyst in which RuO2 can form epitaxial layers on the surfaces of Rutile TiO2, here we have investigated the shape evolution process of RuO2 nanoparticles on the surface of P25 TiO2. It is found that size effects exist in this process and RuO2 nanoparticles with sizes ~sub-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
64
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 34 publications
4
64
0
Order By: Relevance
“…Detailed studies performed by Sumitomo Chemical [60] suggest, that the actual catalyst consists of an ultra thin RuO 2 film (about one monolayer thick [61]) coating the rutile-TiO 2 nano particles, which are preferentially oriented along the (110) direction. The pseudomorphic growth of RuO 2 on TiO 2 is facilitated by the fact that both materials are of crystalline rutile structure with similar unit cell dimensions [62].…”
Section: Configurationmentioning
confidence: 99%
“…Detailed studies performed by Sumitomo Chemical [60] suggest, that the actual catalyst consists of an ultra thin RuO 2 film (about one monolayer thick [61]) coating the rutile-TiO 2 nano particles, which are preferentially oriented along the (110) direction. The pseudomorphic growth of RuO 2 on TiO 2 is facilitated by the fact that both materials are of crystalline rutile structure with similar unit cell dimensions [62].…”
Section: Configurationmentioning
confidence: 99%
“…Therefore, epitaxial growth can be utilized to immobilize metal NPs on support materials, providing potential applications in the development of sintering-resistant supported metal catalysts [23] . It has been reported that epitaxial growth of metal NPs on support can improve the activity, selectivity and/or stability of the catalysts of interest [28][29][30][31][32][33][34][35] . For instance, it was reported that long-term stability of RuO 2 could be maintained during the Deacon reaction if RuO 2 has an epitaxial relationship with the surfaces of rutile TiO 2 and SnO 2 [28][29][30][31] .…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that epitaxial growth of metal NPs on support can improve the activity, selectivity and/or stability of the catalysts of interest [28][29][30][31][32][33][34][35] . For instance, it was reported that long-term stability of RuO 2 could be maintained during the Deacon reaction if RuO 2 has an epitaxial relationship with the surfaces of rutile TiO 2 and SnO 2 [28][29][30][31] . Similarly, Enterkin et al found that growth of Pt NPs onto SrTiO 3 nanocuboids exhibited cube-on-cube epitaxy with a thermodynamically stable configuration and the morphology and selectivity can be tuned precisely in order to achieve the desired catalytic properties [32][33][34] .…”
Section: Introductionmentioning
confidence: 99%
“…6,5 Coupling rutile TiO2 with RuO2 has been widely studied in numerous catalytic reactions due to their lattice matching and strong metal-support interaction. [12][13][14][15][16][17] claimed that RuO2/rutile-TiO2 catalyst exhibited high catalytic activity and thermal stability toward HCl oxidation to Cl2 due to highly dispersed, ultrafine RuO2 crystallites, approximately a single unit-cell thickness, that cover the surface of TiO2 primary particle with strong interaction between RuO2 and TiO2. Xiang et al 15 demonstrated that the redistribution or spreading of RuO2 occurred from a spherical shape (~ sub 2 nm) to epitaxial island layers along the TiO2 surfaces during the chlorination reaction, forming a unique heterostructure at the interface.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16][17] claimed that RuO2/rutile-TiO2 catalyst exhibited high catalytic activity and thermal stability toward HCl oxidation to Cl2 due to highly dispersed, ultrafine RuO2 crystallites, approximately a single unit-cell thickness, that cover the surface of TiO2 primary particle with strong interaction between RuO2 and TiO2. Xiang et al 15 demonstrated that the redistribution or spreading of RuO2 occurred from a spherical shape (~ sub 2 nm) to epitaxial island layers along the TiO2 surfaces during the chlorination reaction, forming a unique heterostructure at the interface. Lin et al 17 elucidated that among several oxide supports including anatase TiO2, rutile TiO2, rutile SnO2, Al2O3 and SiO2, rutile TiO2 was the most appropriate support to enhance the catalytic activity of N2O reduction.…”
Section: Introductionmentioning
confidence: 99%